Methods of logic - Quine, Willard Van Orman (New York Hott Rinehart and winston, 1959)
his widely used textbook of modern formal logic now offers a number of new features. Incorporating updated notations, selective answers to exercises, expanded treatment of natural deduction, and new discussions of predicate-functor logic and the affinities between higher set theory and the elementary logic of terms, W. V. Quine$1 (Bs new edition will serve admirably for both classroom and independent use.s
Keywords: Mathematics; Logical methods